GBA ADVERTISMENT : PENDEKATAN BERBASIS GENRE DALAM PEMBUATAN IKLAN PARIWISATA MAHASISWA VOKASI - Nyoman Ardiana Listriyawati (Universitas Tribhuwana Tunggadewi, 2021)
This study tried to applied the Application of Genre Based Approach to students to write advertisements in English class at Universitas Airlangga. This research was classified as qualitative by trying to find information related to lecturers who applied the Genre Based Approach for third-semester students, modifications made by lecturers in the application of the Genre Based Approach, and the results of student work in responding to the implementation of the Genre Based Approach. This research included describe, recorded, and categorized with observation and interview techniques, where the description of data analysis is presented textually. The results showed that the lecturers have implemented all stages in the Genre-Based Approach with some modifications that are tailored to the needs of students, then all student works have fulfilled the purpose of an advertisement, namely to promote tourist attractions and attract readers to come and visit these places.